2016
DOI: 10.18608/jla.2016.32.7
|View full text |Cite
|
Sign up to set email alerts
|

Analytics for Knowledge Creation: Towards Epistemic Agency and Design-Mode Thinking

Abstract: Innovation and knowledge creation call for high-level epistemic agency and designmode thinking, two competencies beyond the traditional scopes of schooling. In this paper, we discuss the need for learning analytics to support these two competencies, and more broadly, the demand for education for innovation. We ground these arguments on a distinctive Knowledge Building pedagogy that treats education as a knowledge-creation enterprise. By critiquing current learning analytics for their focus on static-state know… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 41 publications
1
22
0
1
Order By: Relevance
“…requirements to compete in certain sectors (Heras-Saizarbitoria et al 2006);(Heras-Saizarbitoria et al 2011); (Adair and Jaeger, 2016); (Gómez-López et al 2019). The results of this study are in line with the results of research by (Chen and Zhang, 2016) that IT (Information Technology) investment is the most important factor in achieveing business success. The competitive advantage that can be achieved depends largely on whether the SMEs will effectively use network technology and the expansion of the size of the business (from SMEs to larger scale business).…”
Section: Managerial Implicationssupporting
confidence: 88%
See 1 more Smart Citation
“…requirements to compete in certain sectors (Heras-Saizarbitoria et al 2006);(Heras-Saizarbitoria et al 2011); (Adair and Jaeger, 2016); (Gómez-López et al 2019). The results of this study are in line with the results of research by (Chen and Zhang, 2016) that IT (Information Technology) investment is the most important factor in achieveing business success. The competitive advantage that can be achieved depends largely on whether the SMEs will effectively use network technology and the expansion of the size of the business (from SMEs to larger scale business).…”
Section: Managerial Implicationssupporting
confidence: 88%
“…Research related MSMEs in Beijing, China on the adoption of the e-commerce and its impact on business success found that IT investment is the most important factor to achieve success, the competitive advantage can be achieved largely depends on whether the company will effectively use network technology; second, expanding the size of the company can encourage an increase in the volume of MSMEs transactions in the short term; third, internet availability has a positive effect on the volume of e-commerce trade, but the intensity is unclear, and the effect is relatively stable (Chen and Zhang, 2016). In addition, research conducted by (Hamad, Elbeltagi and El-Gohary, 2018), suggesting that the technology-organizationenvironment (TOE) framework factor has a significant impact on various levels of B2B e-commerce adoption and has an indirect impact on competitive advantage.…”
Section: Information Technology Adoption and Sustainable Competitive Advantagementioning
confidence: 99%
“…What is (implicitly or explicitly) questioned is whether the default frame of mind for which LA produces data should be that of a rational decision maker (Marzouk et al, 2016). Here, it makes sense to ask whether analytics, first and foremost, should be embedded in learning, as opposed to data about learning (Chen & Zhang, 2016). This would create the design challenge of creating a system that delivers actionable insights into action flows without necessarily demanding rational deliberation outside the flow.…”
Section: Resultsmentioning
confidence: 99%
“…This hierarchical structure has not gone unnoticed. Chen and Zhang (2016) write that In a traditional learning analytic scenario, the learners reside at the bottom of a hierarchy, being treated as "data objects" to be interpreted by "data clients" performed by teachers, institutions, and governmental agencies (Greller & Drachsler, 2012). For example, institutional data are fed into algorithms to predict student success, with resulting predictions delivered to the teacher on demand to trigger intervention (Arnold & Pistilli, 2012).…”
Section: A Simplified Storymentioning
confidence: 99%
“…The present century demands diverse kinds of soft skills to characterize knowledge, develop competences to fulfill diverse tasks, and acquisition of attitudes to profit from learning experiences that prepare students for lifelong learning in a complex, heterogeneous, and dynamic world (Buckingham & Deakin, 2016). For instance, with the aim of developing high-level epistemic agency and design mode thinking competencies, Chen and Zhang (2016) face education as a knowledge-creation enterprise, where LA is inspired in a conceptual model of knowledge-building analytics that embraces agency-driven, choice-based, and progress-oriented analytics. Moreover, qualities that lifelong learners need to succeed (e.g., effort revealed by behavior, diligence, engagement, and persistence) are evaluated by means of visual LA that facilitates a productive dialogue among staff and students (Nagy, 2016).…”
Section: Internalizationmentioning
confidence: 99%